Optical dating of tsunami-laid sand from an Oregon coastal lake - Ollerhead, J.; Huntley, D. J.; Nelson, A. R.; Kelsey, H. M. (Quaternary Science Reviews, 2001)
Optical ages for five samples of tsunami-laid sand from an Oregon coastal lake were determined using an infrared optical-dating method on K-feldspar separates and, as a test of accuracy, compared to ages determined by AMS C-14 dating or detrital plant fragments found in the same beds. Two optical ages were about 20% younger than calibrated C-14 ages of about 3.1 and 4.3 ka. Correction of the optical ages using measured anomalous fading rates brings them into agreement with the C-14 ages. The approach used holds significant promise for improving the accuracy of infrared optical-dating methods.Luminescence data for the other three samples result in optical age limits much greater than the C-14 ages. These data provide a textbook demonstration of the correlation between scatter in the luminescence intensity of individual sample aliquots and their normalization values that is expected when the samples contain sand grains not adequately exposed to daylight just prior to or during deposition and burial. Thus, the data for these three samples suggest that the tsunamis eroded young and old sand deposits before dropping the sand in the lake. (C) 2001 Elsevier Science Ltd. All rights reserved.
500nqTimes Cited:24Cited References Count:39